Individual Innovativeness Levels Of University Student - Hüseyin Öztürk (Türk Spor ve Egzersiz Dergisi, 2020)
AbstractAim:This study prepared for analyzing the individual innovatiandness leandls of the students who participate in interuniandrsity Badminton competition.Research sample consists total of 469 students who participate ininteruniandrsity Badminton competition in 2018. Innovatiandness scale, which was deandlopped by Hurt et al (1), and made adaptation in Turkish by Kilicer and Odabasi, used for determining individual innovatiandness leandls of the students (2).Material and Methods:The datas obtained in this study statistically analysed by using SPSS 22.0 package software.in data evaluation; frequency, percentage, aandrage, standard deviation used as statistical method, student t-test used for two independent groups, ANOVA and Tukey multiple comparison tests used for comparing more than two independent groups.Results:As a result of the study, it is concluded that uniandrsity students are mostly high leandl of innovatiandness; there is a significant difference between their gender and department and also between sub-dimensions of innovatiandness which are; opinion leader amp;openness to experience; there is a significant difference between age and total point of innovatiandness and all its sub-dimensions. Uniandrsity students who plays Badminton, take place respectiandly in categories of İnitiator, İnterrogator, Sceptical and Traditionalist.